Warfarin prescription in patients with nonvalvular atrial fibrillation and one non–gender‐related risk factor (CHA2DS2VASc 1 or 2): A treatment dilemma. Issue 1 (11th November 2017) - Denas, Gentian; Zoppellaro, Giacomo; Padayattil Jose, Seena; Antonucci, Emilia; Marongiu, Francesco; Poli, Daniela; Testa, Sophie; Tripodi, Armando; Palareti, Gualtiero; Pengo, Vittorio
Summary: Introduction: The issue of anticoagulation in individuals with nonvalvular atrial fibrillation (NVAF) and 1 non–gender‐related (NGR) risk factor is subject to debate. The reported risk of stroke in untreated individuals is not uniform, and the rate of hemorrhage associated with anticoagulation in this group of individuals is not well defined. To this end, we assessed the rate of stroke and major hemorrhage in individuals treated with warfarin. Materials and Methods: individuals were extracted from the START register, an observational, multicenter, dynamic inception cohort study that collects data on NVAF individuals starting anticoagulation therapy. Risk of stroke is stratified using the CHA2 DS2 VASc score upon entry into the registry. Results: Overall, 431 individuals with 1 NGR risk factor were followed up for 604 person‐years. One nonfatal ischemic stroke was recorded (0.17 per 100 person‐years) during follow‐up. On the other hand, there were 9 major bleeding events (1.49 per 100 person‐years), with 4 being intracranial hemorrhage (0.66 per 100 person‐years), 1 of which was fatal. No difference in patient characteristics, bleeding risk factors, and quality of treatment were found between individuals who bled versus those who did not. However, a trend toward more bleeding events was observed in individuals <65 years old. Conclusion: We found an elevated risk of major bleeding and intracranial hemorrhage in NVAF individuals treated with warfarin with 1 NGR risk factor for stroke. These data call for caution when treating with warfarin these individuals.